Repression and black holes in Laurent Mauvignier novel about Algerian War - Giacomo Raccis (Between, 2015)
XXth century history obliged narrators to clash with events that was literally inexpressible, measuring the potential and the lack of literary means. Laurent Mauvignier made this confrontarion the centre of his poetics: from minimal, private tragedies to great, historical dramas, passing through the media mystification of absurd fait divers, his novels face the Evil problem and its representation in words.